EFFECT OF THE CONVECTIVE BOUNDARY LAYER ON RADIOSONDE FLIGHT PATH OVER BAGHDAD AIRPORT STATION (CASE STUDY) - A. F. Hassoon; T. O. Roomi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This research was aimed to investigate effect of the convection conditions resulted from surface heating at different weather condition on movement track of radiosonde. Data used in this study divided to surface local weather from Baghdad airport station and reanalysis weather surface data from European center medium weather forecast (ECMWF) that contain also advance parameter parameters such as sensible heat flux and boundary layer height and other, all have large accurate spatial distribution inside and outside Baghdad province. Third type data from radiosonde used to observed atmospheric upper layer through selected days from winter season (January month) and summer season (July month) all at time 12AM. Software installed in radiosonde used to recoded wind speed, temperature and other parameter such as global position system (GPS) all plotted and represented by ArcGISpro. Results show different in the radiosone path at convection and nonconventional conditions. Convection constraint movement of radiosonde path (wind speed profiles very low don’t reach to 30m/s in upper layer, this is opposite to nonconventional case, it reach to more than 65m/s) because turbulent and random in different directions, this case is opposite to the nonconventional condition there is large free movement, where balloon reach to large and upper distance in nonconventional (Jan. cases).